Isolation screening and characterization of nata-producing microorganisms from seaweed pulp (Gracilaria sp.) - Mamaril, Eden F. (University of the Philippines in the Visayas, 1998)
Isolation, screening and characterization of probable nata-producing microorganism was conducted on samples prepared from bleach-dry Gracilaria sp. Probable nata-producing isolate EM23 from fresh pulp extract sample exhibited characteristics smilar to the known nata organism Acetobacteraceti subsp. Xylinum both morphologically and physiologically. Isolate EM23 is capable of producing acceptable quality nata film/pellicle from 30% Gracilaria seaweed pulp extract at pH 5.0, 25% inoculum and 10% sugar at room temperature (28-32 C). Chemically, the nata produced which is cellulosic in nature contains 97.22%, moisture, 0.55% (w/w) crude fiber having a total available carbohydrates (as % glucose of 70.00%. Sensority, nata quality was generally found to be comparable to nata de coco, both raw and cooked, with its texture slightly better than nata de coco. Gracilaria seaweed pulp extract was proven to be a promising/potential source/raw material of both probable nata-producing organisms as starter/inoculum and an acceptable quality nata as a food item.